pH response of pollen paper for drug delivery - Low, Marcus Wei Song (Nanyang Technological University, 2022)
Pollen is one of the most durable natural materials known to mankind. This is attributed to sporopollenin, a component of the pollen grain’s outer walls. There has been much development on pollen paper as a sustainable biomaterial. Pollen paper has kept the ability to undergo reversible shape changes induced by the environment from its microgel form. pH responsive studies on pollen paper have been focused on shape morphing, while little is done on the pH response with regards to drug delivery. When compared to traditional transdermal patches which operate by releasing drugs at a steady rate, pollen paper shows potential in varying the release rate of drugs. This is achieved by leveraging pollen paper’s ability to control swelling through changes in pH, which would allow a change in drug release rate. This study takes some reference from previous research which studied the pH responsive drug delivery of sporopollenin exine capsules.